Persepsi Masyarakat terhadap Status Kawasan Suaka Margasatwa Ko’mara Kabupaten Takalar - Hamdan Hamdan; Amran Achmad; Asar Said Mahbub (Jurnal Hutan dan Masyarakat, 2017)
The management of protected areas and the surrounding community is an inseparable part. Community around the forest area is a component that interacts directly with the forest area. Interaction of the community with the forest area is influenced by the community's perception of the forest itself. This research was carried out at hamlet which bordered directly on Ko'mara Wildlife Reserve. Data collection was done by field observation, interview, questionnaire and study literature. The level of perception is determined by means of scoring techniques and the factors influencing the perception of the community are described descriptively. The results showed that: (1) the public perception on Karemanepasan and Karepatodo hamlet is moderate, while Ballaborong hamlet is low. (2) Age of the respondent in the productive age range, there is still a chance for a change in perception towards better. The low level of education of respondents influences the insight and way of thinking in the perception of the forest area. The work of the interviewees as farmers, who are heavily dependent on forests as water suppliers for their farms, can form a positive perception. Community engagement can be generally positive because the community can be a means of advising the reserve by the Area Manager.